Corona phenomena of various high voltage shielding types - Pattanadech, N.; Potivetkul, S.; Yuttagowith, P. (My University, 2006)
This paper presents the corona phenomena of various high voltage shielding types. The 11 kinds of corona shieldings which were corona steering ring, 7 circular connected half-spheres, topping 2 rings, 4 connected spheres, barrel shape with 5 rings, decagon with 5 rectangles, 2 connected symmetrical rings, drum shape with 2 rings, spherical connected bowls, 3 connected bowls, and 5 connected donuts were designed, constructed and examined. The corona shields made of aluminum were designed for 50 kV rating. In the design process, the electric field distribution and its maximum value of the designed corona shielding were simulated using finite element program. Then the constructed corona shieldings were installed with the high voltage electrode and investigated in the topics of corona inception voltage and partial discharge values at the specified test voltages. The corona shielding characteristic test was carried out at various atmospheres. The tested results are composed of the corona phenomena pictures obtained from the corona camera and elliptical displays showing PD activity and the amplitude of corona discharge taken from the PD detector. The tested results show that the 5 connected donut corona shielding has the best performance. It reduced the corona phenomena of the tested electrode about 20 % after it was installed with the high voltage electrode. The trend of the data tested at 3 various atmospheres are relatively similar. Besides, the results obtained from the simulation program show good agreement with the tested results. © 2006 IEEE.
Keywords: Corona inception voltage; Corona phenomena; High voltage shielding; Partial discharge